Safety of oral immunotherapy for cashew nut and peanut allergy in children – a retrospective single-centre study - Maria Breiding; Maarja Soomann; Michèle Roth; Johannes Trück; Felicitas Bellutti Enders (Swiss Medical Weekly)
AIM OF THE STUDY: Oral immunotherapy (OIT) is increasingly used for the treatment of childhood food allergies, with limited data available on cashew nut OIT. This real-life study investigated the safety and feasibility of cashew nut OIT, comparing it with peanut OIT, with a focus on the up-dosing process.